Design of a wireless wearable DAQ system for the evaluation of sports performances - Bonaiuto, V.; Lanotte, N.; Romagnoli, C.; Silvaggi, N.; Annino, G. (Proceedings, 2018)
An accurate monitoring of the professional athletes` exercises during training sessions is able to improve their performance by helping them in improving the effectiveness of the movement, in the injury prevention and in the rehabilitation protocols. Wearable and non-encumbrance DAQ (Digital Acquisition) systems are required because it is important to collect data from the athlete`s performance in his natural environment rather than in the unspecific spaces of a laboratory. This paper deals with the design of a wireless data logger for the evaluation and analysis of the sport performance. In particular, the system is composed of a multichannel sEMG (surface Electromyography) system synchronized the kinematic signals obtained by an Inertial Measurement Unit (IMU) placed on the back of the athlete by the use of a belt. The system can be wirelessly connected with a proper terminal for data display and analysis.